PENGARUH VIDEO PENDEK YOUTUBE TERHADAP PEMAHAMAN KONSEP IPA SISWA DI SMPN 1 PRAYA TIMUR - Embun Sapira; Muhlis; I Putu Artayasa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning process at SMP Negeri 1 Praya Timur is still monotonous, making some students not interested in studying both when receiving learning material during the pandemic and after the pandemic. This research aims to determine whether there is a difference in the understanding of science concepts of students at SMPN 1 Praya, who take part in learning using short YouTube videos and students who take part in learning without using short YouTube videos. This type of research is a quasi exsperiment with a nonequivalent control group design. The population in this study were Class VIII students at SMP Negeri 1 Praya Timur. With a sample of 64 students who were then divided into 2 classes, namely the experimental class and the control class. The results of the hypothesis test also show a sig value. (2-tailed) is smaller than α, namely 0.009 ˂ 0.05, which means that there is a difference between students' understanding of science concepts at SMPN 1 Praya Timur, who take part in learning using short YouTube videos and students who take part in learning without using short YouTube videos.